Chemical Communication between Heart Cells is Disrupted by Intracellular Renin and Angiotensin II: Implications for Heart Development and Disease - De Mello, Walmor C. (Frontiers in Endocrinology, 2015)
Highlights Intracellular renin and angiotensin disrupts chemical communication in heart. Epigenetic modification of renin angiotensin aldosterone system (RAAS) and heart disease. Intracrine renin angiotensin and metabolic cooperation. Gap junction, intracellular renin and angiotensin, cellular patterns, and heart development. The finding that intracellular renin and angiotensin II (Ang II) disrupts chemical communication and impairs metabolic cooperation between cardiomyocytes induced by aldosterone, hyperglycemia, and pathological conditions like myocardial ischemia is discussed. The hypothesis is presented that epigenetic changes of the renin angiotensin aldosterone system (RAAS) are responsible for cardiovascular abnormalities, including the expression of RAAS components inside cardiac myocytes (intracrine RAAS) with serious consequences including inhibition of electrical and chemical communication in the heart, resulting in metabolic disarrangement and cardiac arrhythmias. Moreover, the inhibition of gap junctional communication induced by intracellular Ang II or renin can contribute to the selection of cellular patterns during heart development.